CITY RESIDENTS' EXPECTATION FOR PERSUASIVE DAKWAH (A Study in Cimahi City) - Bambang Saiful Ma'arif; umar yusuf; Suliadi Suliadi; Parihat Parihat; Seviyenti Fikroh (MediaTor (Jurnal Komunikasi), 2021)
This paper is the result of research on 'Mapping  the  Profile  of Persuasive Da’wah Agenda in Cimahi City'. Cimahi is the smallest city in Indonesia with 3 sub-districts, known as a center for "creative animation." Cimahi residents have various livelihoods, such as laborers, traders, military and civil servants. Good da'wah is delivered based on reliable information, but until now no data has been obtained about the profile of persuasive da'wah in Cimahi City. This research is a survey conducted on 399 respondents with a multistage random sampling technique. The results of the research are as follows: 1) Da'wah actors need to consider the socio-demographic conditions of Cimahi City residents in designing their activities to achieve da'wah objectives optimally; 2) The average residents of Cimahi City has the habit of participating in intense religious activities, especially the Qur’an recitation; 3) Residents of Cimahi City respond positively to da'wah figures, da'wah themes, and da’wah  media; and 4) Residents of Cimahi city have their expectation for da'wah beyond bil-lisan or oral speech, especially recitation, which is seen as being able to increase religious knowledge, religious appreciation and encourage congregational religious practice. They hope da’wah activities can expand to bil-hal (action) on matters such as health, entrepreneurship and community empowerment. Da'wah is persuasive if people like, accept and practice its message. The more preferred/accepted a da'wah, the more persuasive it is.